PENINGKATAN TPACK GURU MATEMATIKA SMK MELALUI PELATIHAN DAN PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN DIGITAL (CANVA DAN MATHCITYMAP) - Fauzi, Moch.; Prasetyo, Puguh Wahyu; Shodiq, Lukman Jakfar; Triayuningtiyas, Alfika; Nandika, Fuja Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The majority of vocational mathematics teachers in Lumajang region provide mathematics materials traditionally using textbooks as learning resources. Whereas the fast development of technology can support the improvement of teachers' Technological Pedagogical Content Knowledge (TPACK). The use of technology such as Canva and Mathcitymap applications makes teaching materials look better, real, and more attractive. It was necessary to improve teachers' soft skills in mastering the Canva and Mathcitymap applications so that their skills in integrating technology in mathematics learning materials also increased. The implementation of this project uses training and mentoring methods for service partners, namely members of the MGMP of vocational mathematics teachers of Lumajang Regency in the odd semester of 2023/2024. Training was conducted online through zoom meetings and mentoring was carried out directly to selected teachers to practice the use of Canva and Mathcitymap. The results of the program showed an increase in mastery the concept of